Business cycles, technology and exports - Dario Guarascio; Mario Pianta; Matteo Lucchese; Francesco Bogliacino (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
This article shows - on both conceptual and empirical grounds - the importance of business cycles in affecting key relationships between innovation and international performance. While periods of upswing are characterised by a well documented 'virtuous circle'. between innovation inputs, new products and export success, during downswings most of the positive relationships and feedbacks tend to break down. The findings of Guarascio et al. (2014) on the long-term relationships between R&D, new products and exports are confirmed and qualified with major novelties. But when the period of analysis is split between periods of upswing and downswing - following Lucchese and Pianta (2012) - significantly different relationships emerge. These results are obtained through an approach that combines several complementary perspectives. A Schumpeterian view on the diversity of technological change allows to disentangle the specificities and effects of innovation inputs and outputs, and of new products and new processes. A structural change perspective on the role of demand as a driver of innovation and on the importance of open economies allows to link industries. dynamics with international competitiveness. A business cycle perspective crossing the two previous appraoches sheds new light on the fragility of key economic relationships and on the long term damage that recessions may cause to the 'virtuous circle'. of innovation and performance. The model we propose links exports, R&D and innovation success in a system of three simultaneous equations allowing for the presence of feedbacks loops among key variables. The empirical test is carried out for the period 1995-2010 at the industry level, on 21 manufacturing and 17 service sectors; country coverage includes Germany, France, Italy, Spain, the Netherlands and the United Kingdom, representing a very large part of the European economy.
Keywords: F41; F43; O31; O33; C3; 330; Business cycles; Innovation; Export; Three Stage Least Squares